Physicochemical Characterization and Dissolution Enhancement of Mefenamic Acid–Isonicotinamide Crystalline Solid Dispersion - Indra Indra; Nurul Apriani; Ade Yeni Aprillia; Winda Trisna Wulandari; Gatut Ari Wardani; Firman Gustaman (Biology, Medicine, & Natural Product Chemistry, 2025)
Poor aqueous solubility limits the bioavailability of non-steroidal anti-inflammatory drugs like mefenamic acid. This study aims to improve the solubility and dissolution of mefenamic acid through crystalline solid dispersions using solvent evaporation and co-grinding techniques with selected co-formers. Solid dispersions were formulated at different drug-to-co-former ratios (1:1, 1:2, and 2:1) and characterized using differential scanning calorimetry, Fourier-transform infrared spectroscopy, and powder X-ray diffraction. DSC results revealed reduced crystallinity, indicated by the disappearance of melting peaks and the appearance of a single glass transition temperature. FTIR analysis confirmed hydrogen bonding between the drug and co-former, while PXRD patterns showed a loss of long-range order, supporting the formation of amorphous phases. Dissolution testing demonstrated a significant increase in drug release, particularly in the 1:2 formulation, which outperformed the pure drug and other ratios. These results confirm that the choice of preparation method and co-former ratio critically influence the performance of solid dispersions. This study provides valuable insights into the design of improved oral formulations for poorly soluble drugs, contributing to the advancement of pharmaceutical technology